1990
DOI: 10.1207/s15327752jpa5501&2_24
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Depression in an Employment Setting

Abstract: This study extends the literature on sex differences in depression to an employment setting, using Minnesota Multiphasic Personality Inventory (MMPI; T and raw scores) and Depression (D) 30 measures. In contrast to previous findings, no gender differences remained on any of the measures after the effects of salary, age, education, and job classification had been taken into account. Findings replicated earlier results showing depressed males to have greater difficulty with concentration and motivation than depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The main findings in the non‐clinical studies were that women tended to report more symptoms than men (6, 8, 11, 14) or that women tended to get higher total scores on depression rating scales (7, 12). In three (9, 10, 13) of the nine studies, however, no gender differences in severity of depression were found. As depression rates consistently have been found to be higher for women than for men (1, 2, 25), the main findings in the non‐clinical samples may be reflecting the overrepresentation of depression among women.…”
Section: Studies On Non‐clinical Samplesmentioning
confidence: 81%
See 3 more Smart Citations
“…The main findings in the non‐clinical studies were that women tended to report more symptoms than men (6, 8, 11, 14) or that women tended to get higher total scores on depression rating scales (7, 12). In three (9, 10, 13) of the nine studies, however, no gender differences in severity of depression were found. As depression rates consistently have been found to be higher for women than for men (1, 2, 25), the main findings in the non‐clinical samples may be reflecting the overrepresentation of depression among women.…”
Section: Studies On Non‐clinical Samplesmentioning
confidence: 81%
“…By evaluation of the recent studies, two major methodological conditions were considered: the population under study and the diagnosis of depression. As regards the population under study, the samples in the studies mentioned were non‐clinical samples (6–14), clinical samples of patients with specific subtypes of depression (15–17) or clinical samples of hospitalized patients (18, 20). As regards the diagnosis of depression, the most recent diagnostic criteria were used in only one study (20) and the ICD‐10 criteria were not used in any of the studies.…”
Section: Recent Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To develop the risk model, a range of risk indicators were identified which have individually been found either to predict depression at follow-up or to be associated with the prevalence of depression in community studies. Relevant risk factors shown in cohort studies to predict depression included in this cohort study were initial depression levels [4,11], use of alcohol [11,12], cannabis use [13-15], smoking [16,17], life events [4,18,19], chronic illness [4], medical illness [4,20], low level of education or low levels of mastery [21], employment status or financial pressure [22,23], religious service attendance [24,25], living alone [5], age and gender [10]. Evidence from intervention trials also point to the importance of physical activity in the treatment of depression [26].…”
Section: Introductionmentioning
confidence: 99%